Influenced tumor microenvironment and tumor immunity by amino acids - Yu, Min; Zhang, Shuang (Frontiers in Immunology, 2023)
It is widely accepted that tumors are a complex tissue composed of cancer cells, extracellular matrix, inflammatory cells, immune cells, and other cells. Deregulation of tumor microenvironment promotes tumor aggressiveness by sustaining cell growth, invasion, and survival from immune surveillance. The concepts that some dietary nutrients could change tumor microenvironment are extremely attractive. Many studies demonstrated that high-fat diet-induced obesity shaped metabolism to suppress anti-tumor immunity, but how amino acids changed the tumor microenvironment and impacted tumor immunity was still not totally understood. In fact, amino acid metabolism in different signaling pathways and their cross-talk shaped tumor immunity and therapy efficacy in cancer patients. Our review focused on mechanisms by which amino acid influenced tumor microenvironment, and found potential drug targets for immunotherapy in cancer.